Translation of Finnish Political History into English - Nybom, Markus (My University, 2025)
The subject of this thesis is the translation of Finnish-language works of political history into English, explored through the lens of cultural ambassadorship, with the intention of discovering the underlying motives that lead to books of political history getting translated from a minor culture to a major one. This topic has, broadly speaking, been largely ignored, with only a couple of studies to its name. This thesis approaches the subject through the analysis of a total of 26 books (the originals and their translations), with the focus being their paratexts, i.e. the parts outside the main text itself, such as the cover, the blurb, possible notes and introductions etc. Through these paratexts I try to ascertain the motives behind the translations, either through explicit statements on them, or by making deductions. The thesis’ purpose is to contribute to historiography and translation studies through this lens. The material indicates that mainly works concerning Finland as an independent nation have been chosen to be translated. Works covering Finland's earlier history as part of other countries were in the minority. The translations were published either by Finnish publishing houses or by various university presses, both Anglophone and Finnish, indicating that the impetus for translating them came from Finland rather than the Anglosphere.
Keywords: translation, non-fiction, historiography, paratext, intercultural communication